Creep and mechanical properties of aluminium A356 composites reinforced with coated and un-coated MWCNTs fabricated using the stir casting method. Issue 9 (13th June 2023) - Pan, Qiaoyu; Yu, Xinping; Yu, Fujin
Abstract : Multi-walled carbon nanotubes (MWCNTs) possess outstanding physical and mechanical properties, making them suitable as reinforcing materials for metal-matrix composites. However, their creep resistance has not been studied well. In the present study, aluminium A356 composites reinforced with various weight percentages of MWCNTs were fabricated using the stir casting technique. The surface coating was applied to enhance the wettability of carbon nanotubes. Tensile experiments, fracture analysis, creep tests, and microstructural analyses were performed on the produced composites. Aluminium samples reinforced with 0.2 weight percentage of coated MWCNTs showed to have higher hardness (14%), yield strength (36%), ultimate tensile strength (20%), elongation at break (16%), and creep resistance (30%) compared to that of composites reinforced with uncoated MWCNTs.